Rancang-bangun Pengendali On/Off Nebulizer Berbasis Sensor Fotodioda, Komparator, dan Relay - Arta Bayti Bonita; Amir Supriyanto; Arif Surtono (Jurnal Penelitian Sains, 2018)
Nebulizer compressor has been realized. It utilizes photodiode, LED, comparator, and relay as a control on/off nebulizer. It stops working if the sensor detect asthma drug liquid running out. Relay will work if it get input voltage 3 V (high) of comparator circuit which is used to control compressor. Reference voltage of comparator is 2.98 V.